Iptek berbasis masyarakat melalui program JIBAS (jaringan informasi bersama antar sekolah) dalam pengelolaan perpustakaan sekolah - Putri Rosyadi, Alfiani Athma; Kusumawardana, Adi Slamet (University of Islam Malang, 2021)
Library is one of the learning resources that can be used by students to find the information needed. However, based on the result of observations obtained the fact that students are not attracted to the library because they have difficulty in finding the book they are looking for. This is because the management of books in the school still uses manual book data collection. Based on these problems, IT-based library management is one of the solutions offered. JIBAS is a network of school information systems that are integrated into assisting school management. One application that is available at JIBAS is SIMTAKA which is an application that helps schools manage data and library activities. The activity was started with the JIBAS program training by the Community Service Team. After the training, the activity continued with mentoring activities. This assistance was carried out in schools by testing the use of the JIBAS program in library management. The next activity is the implementation of the JIBAS program where partners have used the program in three months. The last activity is the reflection. In this activity, there is an exchange of information and experience during library management using the JIBAS program for three months. Suggestions for the next activity can be developed JIBAS for school finance and management.